Regulation of gap junctions by protein phosphorylation - Sáez,J.C. (1998)
Gap junctions are constituted by intercellular channels and provide a pathway for transfer of ions and small molecules between adjacent cells of most tissues. The degree of intercellular coupling mediated by gap junctions depends on the number of gap junction channels and their activity may be a function of the state of phosphorylation of connexins, the structural subunit of gap junction channels. Protein phosphorylation has been proposed to control intercellular gap junctional communication at several steps from gene expression to protein degradation, including translational and post-translational modification of connexins (i.e., phosphorylation of the assembled channel acting as a gating mechanism) and assembly into and removal from the plasma membrane. Several connexins contain sites for phosphorylation for more than one protein kinase. These consensus sites vary between connexins and have been preferentially identified in the C-terminus. Changes in intercellular communication mediated by protein phosphorylation are believed to control various physiological tissue and cell functions as well as to be altered under pathological conditions.